ChemInform Abstract: Chiral Room Temperature Ionic Liquids as Enantioselective Promoters for the Asymmetric Aldol Reaction. Issue 9 (March 2015) - Gonzalez, Laura; Escorihuela, Jorge; Altava, Belen; Burguete, M. Isabel; Luis, Santiago V.
Abstract Chiral ionic liquids (CIL), derived from natural amino acids, are used as reaction media for direct asymmetric aldol reactions catalyzed by L‐proline.